2014
DOI: 10.1007/s10822-014-9754-y
|View full text |Cite
|
Sign up to set email alerts
|

New insight in the structural features of haloadaptation in α-amylases from halophilic Archaea following homology modeling strategy: folded and stable conformation maintained through low hydrophobicity and highly negative charged surface

Abstract: Proteins from halophilic archaea, which live in extreme saline conditions, have evolved to remain folded, active and stable at very high ionic strengths. Understanding the mechanism of haloadaptation is the first step toward engineering of halostable biomolecules. Amylases are one of the main enzymes used in industry. Yet, no three-dimensional structure has been experimentally resolved for α-amylases from halophilic archaea. In this study, homology structure modeling of α-amylases from the halophilic archaea H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Therefore, the coil regions in APrBL provide a flexible conformation enhancing its activity and stability under the saline and alkaline conditions. On the contrary, non-halophilic enzymes contain more α-helix and β-strand-forming regions (Zorgani et al, 2014). A similar trend was observed in an alkaline protease from B. pumilus (Baweja et al, 2016).…”
Section: Secondary and Three-dimensional Structure Modeling Of The Aprblsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, the coil regions in APrBL provide a flexible conformation enhancing its activity and stability under the saline and alkaline conditions. On the contrary, non-halophilic enzymes contain more α-helix and β-strand-forming regions (Zorgani et al, 2014). A similar trend was observed in an alkaline protease from B. pumilus (Baweja et al, 2016).…”
Section: Secondary and Three-dimensional Structure Modeling Of The Aprblsupporting
confidence: 61%
“…The SOPMA tool revealed that the APrBL contained 31.75% α-helices, 22.55% β-strands, and 45.70% coils, suggesting the dominance of the coils. The halophilic and alkaliphilic enzymes need to maintain a balance between enough rigidity to prevent the unfolding and flexibility to allow the motions necessary for the catalysis (Zorgani et al, 2014). Therefore, the coil regions in APrBL provide a flexible conformation enhancing its activity and stability under the saline and alkaline conditions.…”
Section: Secondary and Three-dimensional Structure Modeling Of The Aprblmentioning
confidence: 99%
“…Another property is that haloarchaeal amylases have lower propensity for helix formation but higher propensity for coil formation, which keeps amylases being active in high salt concentration through highly negative charged surface with over representation of acidic residues (Liu et al 2011 ; Zorgani et al 2014 ). This haloadaptation in hypersaline environments can be tracked in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…a-amylases form H. marismortui (Zorgani et al 2014), xylanase from Planococcus sp. SL4 (Huang et al 2015b) and protease from Halobacterium sp.…”
Section: Enzyme Adaptationsmentioning
confidence: 99%